Physical Exercise to Combat Academic Burnout in Students - Asif Ali; Muhammad Azam; Asad Hussain Shaikh (The Sky, 2020)
The purpose of this analytical study was to synthesize existing evidence relating to the association of exercise or physical activity with academic burnout in students. Relevant articles were systematically and rigorously searched using ten research databases. Following screening for relevancy, ten studies (eight cross-sectional, one cohort, and one interventional) were selected to include for final synthesis. All of the cross-sectional studies had good or satisfactory quality ratings, and the cohort and interventional studies included in this review had moderate to strong quality ratings.  Six out of eight cross-sectional studies showed an inverse relationship of physical activity or exercise with academic burnout with the exception of two studies showed no significant associations. The cohort and interventional studies also demonstrated negative relationships of physical activity with academic burnout.  The findings are likely to provide some evidence that physical activity may be capable to reduce academic burnout in students.